A Glimpse into the Initial Microsecond of Biomolecular Condensation - Longchen Zhu; Guohong Liao; Yumeng Zhang; Yinfeng Guo; Junlin Chen; Shuqi Zhou; Zhili Wu; Yanan Huang; Xingyu Lu; Chunlai Chen; Hailong Chen; Yuxiang Weng; et al. (Journal of the American Chemical Society, 2026)
Abstract Biomolecular condensation is a key process for cells to maintain their normal physiological activities. However, the process of phase transition remains mysterious, especially for the initial moments of condensation. Herein, we investigated the first microsecond of peptide condensation through temperature jump infrared spectroscopy and molecular dynamics simulations. These techniques overcome the limited spatiotemporal resolution of traditional approaches, allowing us to capture the molecular events and kinetic information on the initial moment for phase transition. The results reveal that structural transitions and early assembly of intrinsically disordered proteins occur on ultrafast time scales. Unexpectedly, backbone hydrogen bonding emerges as the overlooked key mediator to stabilize the local structure for the ultrafast condensation of hydrophobic polypeptides compared to hydrophobicity. By locking local structures, hydrogen bonds help to form more stable interaction interfaces. These findings indicate that hydrogen bonding could enable hydrophobic disordered proteins to adopt preorganized conformations in response to environmental stimuli and serve as a key factor in mediating the assembly kinetics in complex cellular environments.